A long-term solution for shoreline evolution induced by wave action - Mustafa, Mamat; Mohammad Fadhli, Ahmad; Subiyanto, Subiyanto (HIKARI Ltd., 2015)
In this paper new approach of numerical schemes for the shoreline evolution in the long-term scale are presented, and comparisons to analytical solution for some cases are presented for a satisfactory level of suitable numerical scheme. Analytical solutions of shoreline evolution for simple configuration are presented under idealized wave condition. In this study, we also present the shoreline evolution to response the wave height breaking at different value and case. The simulation of shoreline evolution conducts at different of shoreline configuration, which rectangular cut in beach and straight impermeable groin. The simulation result shows that shoreline with straight impermeable groin and finite rectangular beach fill configurations have bigger root mean percentage square error (RMSPE) when the sediment transport rate and time are increased. However the increases of RMPSE is very small which only approximate in the range of 0.1– 0.2 %. In addition, simulations in variation of wave height breaking show that wave height breaking increases the RMSPE increase for both of shoreline configurations. In general the RMSPE shows less than 1% for all cases. These results indicate that this new approach of numerical scheme is very reliable for solving problems of long term shoreline evolution.